Problematika Pengaturan Tindak Lanjut Putusan Mahkamah Konstitusi Dalam Perkara Pidana Oleh Mahkamah Agung - Ni'matul Huda (Fakultas Hukum Universitas Islam Indonesia, 2020)
There are several decisions of the Constitutional Court (MK) regarding judicial review which are not only difficult to implement in practice but also followed-up in a variety of ways. Several norms in the Criminal Code (KUHP) and the Criminal Procedure Code (KUHAP), are some of those that are often petitioned for review at the Constitutional Court. There are two main problems in this paper, first, how is the implementation of the Constitutional Court decision in a criminal case followed-up by the Supreme Court (MA)? Second, how should the Supreme Court's decision follow-up in criminal cases? This study concludes, first, the follow-up after the Constitutional Court's decision (especially judicial review) in criminal cases by the Supreme Court in the form of Supreme Court Circular Letter (SEMA), Supreme Court Regulations (PERMA), and there are even those who ignore the Constitutional Court's decision because the Supreme Court’s decision still rests on the provisions that have been canceled by the Court. Second, to follow-up on the Constitutional Court's decision by the Supreme Court in a criminal case, a legal product in the form of a Supreme Court Regulation must be issued. This is necessary for the smooth running of the judiciary or to fill legal gaps and loopholes resulting from the Constitutional Court's decision. For this reason, the People's Representative Council (DPR) and the Government should immediately revise the Criminal Code and Criminal Procedure Code so as not to create a legal vacuum, so as to provide justice and legal certainty for the community.